Perceived Quality on Purchase Intention of New Brand: How Do Customers Use Brand Recognition and Brand Familiarity? - Muhammad Umar Faruq (Indonesian Scientific Publication, 2024)
This research aim to explore a conceptual model regarding how to attract purchase intention of new brand through brand recognition and familiarity, as well as the mediating role of perceived quality factor. This empirical research adopts an explanatory quantitative approach Structural Equation Model (SEM) based on Partial Least Square (PLS) using the SmartPLS 4 program as the data analysis method. The respondents in this study were 267 people selected using purposive sampling technique with the criteria of those who have consumed products of Mako Cake and Bakery in Semarang City. The results indicate that brand recognition, brand familiarity, and perceived quality have a positive and significant impact on purchase intention of new brand. The findings of this research could be benefical for new brand entities as a guideline in determining appropriate strategies to capture consumer hearts or attract purchase intention by establishing brand recognition and familiarity, thus fostering a positive brand perception. As a new brand, brand recognition and familiarity serve as fundamental prerequisites to generate purchasing intention. Consumers also use perceived quality in shaping their purchasing intention towards new brand, where perceived quality can be formed from consumers' recognition and familiarity with the brand. This also related to consumer behavior towards purchase intention on new brand, consumers may opt to purchase on established and popular brands, yet they also have a curiosity to explore new brands influenced by their perception that new brands offer better quality.